Effect of ph and glycerol waste amount on the glycerol recovery - Nurul Afida, Makhtar (2010)
The objective of this research is to obtain the highest recovery of glycerol based on pH and waste volume. Usually, glycerol residue will be dumped into landfill and can give effect to the environmental pollution. The recovered of glycerol will be produced more valuable product such as for medical, pharmaceutical and succinic acid production. The glycerol residue was taken from the by product of biodiesel production. In this research, the experiment has been run with nine different pH which are from pH 1 until pH 9 and five different amount of sample used which are from 80ml until 160ml. Result from the analysis using HPLC showed that the highest recovery of glycerol was at pH 5 and 140ml of sample used. Increased in pH (after pH 5.0) and glycerol residue (after 140 ml) resulted in decreased in glycerol recovery.